Phonological Adaptation of Hokkien Loanwords in Indonesian - Uti Aryanti (Makassar State University, 2021)
Abstract. The Chinese loan words in Indonesian mainly come from the Hokkien. Many scholars have studied the Hokkien loanwords in Indonesian, but they analyzed from the perspective of semantics and culture, and there is still little research on phonological adaptation. This research attempts to answer three questions, namely, what phonological adaptation do the Hokkien loanwords in Indonesian have in the process of being accepted? Are there sound correspondences between Hokkien loanwords in Indonesian? What are the phonological rules for phonological adaptation of Hokkien loanwords in Indonesian? This research is mainly based on the literature method and comparative research method. Data were collected through literature search and recording. The collected data were processed for natural hearing, a comparative analysis of two Indonesian Hokkien speakers' sound production, and four Indonesian speakers' sound production is conducted. The sound production of the speakers are segmented and coded manually using Praat Version 6.0 (Boersma & Weenink, 2015) focused on the measurements of the acoustic parameters of the sounds produced differently by the two groups of informants and, finally, summed up. Since Indonesian has a more uncomplicated vowel system and a different consonant inventory, when we look at the Hokkien loanwords in Indonesian, we will observe many substitution rules. To maintain the Indonesian syllable structure and phonological restrictions, the Indonesian phonological rules that appear in certain environments are considered to apply to Hokkien loanwords.Keywords: Language contact, Hokkien loanwords, Phonological adaptation